Fatty acid composition and total lipid content of seed oil from three commercial pomegranate cultivars - Hernández F.; Melgarejo P.; Olías J.M.; Artés F. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
Pomegranate seeds are mainly consumed fresh, although in recent years it is used as an ingredient for jam, soft and alcoholic drinks, etc. New applications of pomegranate seeds for fresh consumption and possible industrial use of oil seeds should be sought. Consumers are particularly concerned with the saturated to unsaturated fatty acid ratio, as well as essential fatty acids (linoleic, linolenic and arachidic), with special emphasis on polyunsaturated fatty acids. The main aim of the work was to determine the total lipid content and the fatty acid composition of three commercial pomegranate cultivars, grown under homogeneous conditions. In the seed oils of all varieties studied, only five fatty acids have been identified and the profile of the fatty acid composition was quite similar. The highest levels were those of polyunsaturated fatty acids, with about 90 per cent, and between 60-80 per cent were C18:3 fatty acids with double bonds in position 9, 11 and 13, called punicic acids.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)